The Analysis of Communication Skills on Biology Learning Process with Creative Learning in Senior High School - Erika Arifiana; Suratno Suratno; Dwi Wahyuni (Eduvest - Journal of Universal Studies, 2022)
This article discusses how high school students' creative learning in Biology learning to improve Communication Skills. Creative learning is learning that puts the teacher forward in facilitating learning activities, so that the learning atmosphere is conducive. Communication Skills is the extent of the use of the mind in solving problems by using its thinking skills at a higher cognitive level. This type of research is development research (Research and Development), which is used as concrete evidence in increasing Communication Skills with creative learning involving 10 schools, both public and private schools, and 10 Biology subject teachers as a needs analysis. Retrieval of need assessment data using a questionnaire technique through Google Form given to high school biology teachers. The results of the need assessment show that teachers who always improve students' creative learning by 70%, implementation of the Problem Solving learning model by 30%. Teachers still have difficulties in implementing Problem Solving learning to improve creative learning by 80%. Conclusion SCICR learning can be used to increase Communication Skills and creative thinking in students. Teachers still have difficulties in implementing Problem Solving learning to improve creative learning by 80%. Conclusion  SCICR learning can be used to increase Communication Skills and creative thinking in students. Teachers still have difficulties in implementing Problem Solving learning to improve creative learning by 80%. Conclusion SCICR learning can be used to increase Communication Skills and creative thinking in students.